Composite electrodes for ceria-carbonate intermediate temperature electrolytes - Pereira, J. R. S.
Composite electrodes based on several ceramic oxides were tested for their chemical compatibility and electrochemical performance in systems based on composite Gd-doped ceria + alkaline carbonate electrolytes. Reactivity tests performed at 700 degrees C (accelerated testing conditions), involving the ceramic electrode materials and one mixture of Na and Li carbonates, identified two promising perovskyte-type ceramics, LaCoO3 and La0.8Sr0.2Co0.2Fe0.8O3, as the most stable. Co-pressed and co-sintered cell assemblies (electrode/electrolyte/electrode) involving composite electrodes (perovskytes mixed with alkaline carbonates)were studied in detail by scanning electron microscopy and tested by impedance spectroscopy in air in the temperature range 300-600 degrees C. These tests showed the potential of these composite electrodes for intermediate temperature applications, clearly surpassing in performance standard Au electrodes, here used as reference. (c) 2012 Elsevier Ltd. All rights reserved.